Producer’s vulnerabilities to Global Environmental Change: climate, water, economy and society - Mussetta, Paula; Barrientos, María Julia (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2015)
The paper addresses vulnerability to Global Environmental Change of rural producers of Mendoza River basin, in Argentina. Vulnerability is a complex phenomenon that is generated at the intersection of environmental, social and economic dimensions. From a qualitative study based on in-depth interviews with producers of the study area, the paper explain the processes affecting actors (exposures / sensitivities) and the practices (adaptations) they develop to address these phenomena. The main idea is that hydroclimatological events act on a number of previous, long-term vulnerabilities defined by access to resources. Also it shows that resources are critical to the development of adaptive capacities, but finds that "availability of resources" and "capacity building" are not phenomena always related by a linear and direct causality. That is, sometimes the mere existence of resources is not enough to foster adaptive capacities. Noting some capacities gaps, the article identifies critical factors that could improve rural actors’ capacities and could strengthen them to cope with future global climate events and other factors that affect their living conditions.